Aprendimos a convivir con los senderistas y militares»: Violencia política y respuesta campesina en Huamanquiquia, 1980-1993 - Aroni Sulca, Renzo Salvador (2006)
This study reconstructs the political violence that stroke the Andean communities of the district of Huamanquiquia, in the province of Victor Fajardo, centralsouthern part of Ayacucho. The presence of armed actors in these communities polarized the peasants and had terrible consequences for the community organization and the safety of its members. Their possibilities of cohesion were weakened during the critical years of war, ancient inter and intra community conflicts arose and permeated the social process of violence. During this process, the peasants of Huamanquiquia managed to survive adapting themselves to the circumstances of war and to the political objectives of the armed sectors. This could be considered as a type of peasant response of adaptation-in-resistance.